Weed Infestation and Control on a Miscanthus giganteus Plantation in the Marginal Lands of Ukraine - Makukh, Yaroslav; Макух, Ярослав Петрович; Remeniuk, Svitlana; Ременюк, Світлана Олегівна; Moshkivska, Snizhana; Мошківська, Сніжана Володимирівна; Tkalich, Yurii; Ткаліч, Юрій Ігорович; Rudakov, Yurii; Рудаков, Юрій Миколайович; Tkalich, Olga; Ткаліч, Ольга Вікторівна; et al. (Union of Scientists in Bulgaria – Plovdiv University of Plovdiv Publishing House, 2021)
The research was carried out on the waterlogged marginal lands in the zone of unstable moisture of the Central Forest-Steppe of Ukraine. The generalization of the dynamics of changes in the number of weeds in the miscanthus plantations of the first year of growing allows to divide the growing season into three specific periods. The dynamics of weed infestation in Miscanthus x giganteus J.M. Greef et Deuter ex Hodk. et Renvoize plantations of the first and subsequent years of growing, monthly accumulation of weed green mass starting from 10 th June was studied. The number of weeds in the plantations of miscanthus increased most intensively in the period fromthe middle of May to early June. In subsequent periods, with the achievement of full projective coverage of the field by plants, the intensity of new weed seedlings' appearance decreased. The most abundant weed species were Echinochloa crus-galli (L.)P. Beauv., Setaria glauca (L.) P.Beauv., Thlaspi arvense L., Sinapis arvensis L., Sonchus arvensis L., and Chenopodium album L. All considered herbicides showed the highest level of toxic action to the seedlings of annual cereal weed species. Seedlings of perennials Sonchus arvensis L., Cirsium arvense (L.) Scop. have not been affected by soil herbicides. The following herbicides: Master Power OD at an application rate of 1.5 l/ha (efficiency 95.0%) or Milagro 040 SC at an application rate of 1.25 l/ha (efficiency 88.0%.) are recommended during the season of plant vegetation. Дослідження проводили на заболочених окраїнах у зоні нестійкого зволоження Центрального Лісостепу України. Узагальнення динаміки зміни чисельності бур’янів у насадженнях міскантусу першого року вирощування дозволяє розділити вегетаційний період на три окремі періоди. Динаміка забур’яненості Miscanthus x giganteus J.M. Greef et Deuter ex Hodk. et Renvoize насадженнях першого та наступних років вирощування досліджували щомісячне накопичення зеленої маси бур’янів починаючи з 10 червня. Найбільш інтенсивно чисельність бур’янів у насадженнях міскантусу зростала в період із середини травня до початку червня. У наступні періоди з досягненням повного проективного покриття поля рослинами інтенсивність появи нових сходів бур’янів зменшувалася.
Забур’яненість та боротьба з бур’янами на плантації Miscanthus giganteus в маргінальних землях України
Keywords: miscanthus; міскантус; weeds infestation; забур'яненість; herbicides; гербіциди; marginal lands; маргінальні землі